THE PHARMACOKINETIC PROFILE OF BUPIVACAINE IN NORMOTENSIVE PREGNANT PATIENT DURING CAESAREAN SECTION - Dita Ayulia Dwi Sandi; Djoko Wahyono; Farida Hayati; Yusmein Uyun (Faculty of Pharmacy, Universitas Gadjah Mada)
Bupivacaine is used as a local anesthetic with Epidural Lumbal Anasthesia (ELA) for Caesarean Section (CS) in Indonesia. During pregnancy, there are changes in pharmacokinetic parameter values, as a result of changes in the physiology of the body. This study was designed to determine the pharmacokinetic parameters of isobaric bupivacaine 0.5% with non-compartment model and to monitor its effectiveness. The study was conducted on 7 normotensive pregnant patients who treated with 0.5% bupivacaine doses 75 mg at Integrated Central Surgery Building in Dr. Sardjito Hospital. Blood samples (3 mL) from each patients were drawn at the following intervals: 0, 15, 20, 25, 30, 45, 60, 75 and 90 minutes, then the plasma bupivacaine consentration were measured using HPLC and pharmacokinetic parameters were calculated with non-compartment models, i.e. AUC(0- ), AUMC(0- ) and the MRT. Monitoring the effectiveness was conducted by Pinprick test. Relationship of AUC(0- ) with maximum sensory block was analyzed by Pearson correlation. The results of pharmacokinetic parameters of isobaric bupivacaine 0.5% for 7 normotensive pregnant patients with non-compartment model were AUC(0- ) 101,25 ± 15,07 μg.mL-1.min; AUMC(0- ) 6.431,92 ± 2.212,96 μg.mL-1.min2 and MRT 63,74 ± 20,52 minutes. Bupivacaine 0,5% doses 75 mg as an anesthetic for CS with ELA in 7 normotensive pregnant patients was effective for pain blockade, with maximum sensory block was T6. There was no correlation between AUC(0- ) and sensory block (p>0,05).Keywords: Bupivacaine 0.5%, Sectio Caesarea, Pharmacokinetics, Sensory bloc